Evaluation of word recognition and word recall with bone conduction devices: do directional microphones free up cognitive resources? - Westover, Lindsey; Ostevik, Amber; Aalto, Daniel; Cummine, Jacqueline; Hodgetts, William E. (International Journal of Audiology, 2020)
Objective: To determine if directional microphones improve cognitive capacity in typically hearing adults. The study objectives are to evaluate differences in (1) speech recognition and (2) working memory through a word recall task between bilateral directional and omnidirectional microphone settings. Design: A conductive hearing loss was artificially induced while participants wore bilateral bone conduction hearing aids on softbands. For each hearing aid setting (bilateral omnidirectional and bilateral directional), seven blocks of seven sentences from the Hearing in Noise Test (HINT) were presented at a signal-to-noise ratio of +2 dB. Participants repeated each sentence aloud and after each block, wrote down as many of the last words as they could recall. Study sample: Thirty-five typical hearing adults and a subset (n = 20) achieving ≥80% recognition. Results: The directional microphone setting showed significant improvement over the omnidirectional setting for recognition and recall for both the full set of participants and the subset of participants with ≥ 80% recognition. Conclusions: This study demonstrated that features such as directional microphones can improve both speech recognition and working memory. Even in listening situations where participants can understand the majority of speech, directional microphones may offer improvements to cognitive capacity and reduce listening effort.